PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP VOLUME OKSIGEN MAKSIMAL (VO2 MAKS) TIM SEPAKBOLA NAGARI DURIAN TINGGI KECAMATAN KAPUR IX - Yedo Afri Sandi (JURNAL STAMINA, 2019)
The problem in this study is the low endurance of the Nagari Durian Tinggi football team, seen on 15 January 2019 the High Durian Nagari football team held an event and researchers saw resistance durability especially when passing opponents, driving the ball then Passing and Heading due to a decrease in power hold it especially in the middle of the second half the player does not move like the first half. This study aims to determine whether there is an influence from the provision of circuit training to the maximum volume of oxygen (Vo2 Max) Nagari Durian College football team Kapur IX.This type of research is a quasi-experimental. Located in Limestone IX, conducted in March - April 2019. The population in this study amounted to 38 people. Sampling uses a porposive sampling technique with a total of 20 people. The instrument used in this study is Yo - Yo Test. The data analysis technique used in this study used the t-Test. The results of processing data in this study are tcount> ttable = 289.42> 1.73, The results of this study prove that there is a significant (increasing) effect of giving circuit training to maximum oxygen volume (Vo2 Max) Nagari Durian Tinggi football team in Kapur District IX. meaning that the circuit training treatment applied by the writer can increase the ability of maximum oxygen volume (Vo2 Max). So the circuit training applied by the author can be used in the training process with the aim of increasing Vo2 Max.